Kajian Kritis Terhadab Kebijakan Pemerintah Dalam Pengembangan Bank Syari’ah Di Indonesia - Ahmad Mukhlishin; Aan Suhendri (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
The development of sharia banking in Indonesia is a manifestation of the demand of the people who need an alternative banking system which in addition to providing healthy banking / financial services, also fulfill the principles of sharia. The development of a politically-based Islamic banking system in Indonesia is finally recognized as part of the national development goal of achieving a just and prosperous society based on economic democracy. It is marked by the active role of government in developing sharia banking industry which is expected to be the first step for the development of economic system will be able to be the first step for the development of economic system based on the value of justice, togetherness, equity and expediency. Shari'ah economic system is increasingly known in the society today. Not only for the Islamic community alone, but also for those who are non-Muslims. This is marked by the increasing number of customers in banks that apply the concept of sharia. Seeing this development, it is possible in the future all aspects of the economy will be based on shari'ah. This shows that Islamic values are acceptable in many circles because they are universal, not exclusive and of course have competitive output with conventional banking.